Long Intergenic Non-protein Coding RNA 511 in Cancers - Wang, Xiao-Fei; Liang, Bo; Chen, Cheng; Zeng, Da-Xiong; Zhao, Yu-Xiu; Su, Nan; Ning, Wei-Wei; Yang, Wen; Huang, Jian-An; Gu, Ning; Zhu, Ye-Han (Frontiers in Genetics, 2020)
Background: Long intergenic non-protein coding RNA 511 (LINC00511) is upregulated in various cancers and involved in prognosis. This study aimed to assess the prognostic value of LINC00511 in cancer patients. Methods: We searched Medline, Embase, and Web of Science to identify published studies evaluating the prognostic value of LINC00511 in cancer patients. Analysis of the association between LINC00511 and clinicopathological characteristics was conducted. GEPIA was used to validation and functional analysis and LnCeVar was used to get genomic variations. Results: A total of 9 studies were included. The combined results showed LINC00511 was significantly associated with decreased OS (HR = 3.18, 95% CI = 2.29 ~ 4.42, P < 0.001) albeit with mild heterogeneity (I2 = 58.1%, Ph = 0.014), similarly in cancer type subgroups: breast cancer, digestive system cancer, and cervical cancer (all P < 0.001). There is no publication bias and meta-regression indicated follow-up time maybe heterogeneity of the results (P = 0.008). Additionally, LINC00511 appeared to be correlated with age, clinical stage, tumor size, and lymph node metastasis. Those findings were confirmed in GEPIA. Through LnCeVars, gene ontology and functional pathways were enriched, and dysregulated hallmarks and related ceRNA network of LINC00511 were disturbed. Conclusions: LINC00511 could be predictive of poor OS and lymph node metastasis in multiple cancers, in another word, LINC00511 serves as an unfavorable prognostic factor, and its mechanism is related to ceRNA.